Longing for the Lost Caliphate : A Transregional History - Mona Hassan (New Jersey Princeton University Press, 2016)
In the United States and Europe, the word caliphate has conjured historically romantic and increasingly pernicious associations. Yet the caliphates significance in Islamic history and Muslim culture remains poorly understood. This work explores the myriad meanings of the caliphate for Muslims around the world through the analytical lens of two key moments of loss in the thirteenth and twentieth centuries.
Include Index
Keywords: Caliphate -- Islam and state -- History